Bendungan ASI pada Ibu Postpartum - Tengku Sri Wahyuni (FORUM ILMIAH KESEHATAN, 2019)
Disruption to the lactation process in the form of engorgement can cause the failure to provide exclusive breast milk. Due to Riskesdas report, pattern and percentage of babies aged 0 months in terms of breastfeeding history are grouped into three categories exclusive breastfeeding (39.8%), predominant breastfeeding (5.1%), and partial breastfeeding (55.1%). The purpose of this study was to provide midwifery care for Mrs. L with engorgement in BPM-RM Pematangsiantar city in February-March 2019. This study used a case study design in Mrs.L who was 25 years old, P1Ao with engorgement, data collection through history taking and physical examination. Midwifery care for handling engorgement was 3 times client visits, get breast care and education about lactation management and other obstetric care according to the needs. Postpartum care still given according to the standard until 6 weeks postpartum period after the intervention, the engorgement wais resolved and there were no other lactation disorders. While providing care, no diagnoses were found and potential problems occur for the mother and baby. Education about breast care and lactation management needs to be given since pregnancy so that exclusive breastfeeding can be achieved. Keywords: engorgement; postpartum ABSTRAK Gangguan pada proses laktasi berupa bendungan ASI dapat menyebabkan ketidakberhasilan pemberian ASI ekslusif. Berdasarkan laporan Riskesdas, pola dan persentase bayi berumur 0 bulan ditinjau dari riwayat menyusui dikelompokkan menjadi tiga kategori yaitu menyusui eksklusif (39,8%), menyusui predominan (5,1%), dan menyusui parsial (55,1%). Tujuan penelitian ini adalah untuk memberikan asuhan kebidanan pada Ny.L dengan bendungan ASI di BPM-RM Kota Pematangsiantar pada bulan Februri-Maret 2019. Penelitian ini menggunakan desain studi kasus pada Ny.L 25 tahun, P1Ao dengan bendungan ASI. Pengumpulan data melalui anamnesa dan pemeriksaan fisik. Asuhan kebidanan untuk penanganan bendungan ASI dengan 3 kali kunjungan, klien mendapatkan asuhan perawatan payudara dan edukasi tentang menajemen laktasi serta asuhan kebidanan lain sesuai kebutuhan. Asuhan postpartum tetap diberikan sesuai standar sampai 6 minggu masa postpartum. Setelah intervensi, bendungan ASI teratasi dan tidak terjadi gangguan laktasi lainnya. Selama memberikan asuhan tidak ditemukan diagnosa dan masalah potensial pada ibu dan bayinya. Edukasi tentang perawatan payudara dan manajemen laktasi perlu diberikan sejak masa kehamilan sehingga pemberian ASI eksklusif dapat tercapai. Kata kunci: bendungan ASI; postpartum